Irreducible finite-size effects in surface free energies from crystal-nucleation data - Zykova-Timan, T; Valeriani, C; Sanz, E; Frenkel, D; Tosatti, E (arXiv.org, 2011)
In this Letter we report a simulation study in which we compare the solid-liquid interfacial free energy of NaCl at coexistence, with the value that follows from the height of the homogeneous nucleation barrier. We find that the two estimates differ by more than 100%. Similar, although smaller discrepancies are found for crystals of hard-sphere colloids and of Lennard-Jones ("argon") particles. We consider a variety of possible causes for this discrepancy and are forced to conclude that it is due to a finite-size effect that cannot be corrected for by any simple thermodynamic procedure. Importantly, we find that the surface free energies that follow from real nucleation experiments should be subject to large finite size effects. Taking this in to account, we obtain quantitative agreement between the simulation data and the surface free energy of NaCl that follows from nucleation experiments. Our finding suggests that most published solid-liquid surface free energies derived from nucleation experiments will have to be revised.